2007
DOI: 10.1074/jbc.m610790200
|View full text |Cite
|
Sign up to set email alerts
|

Nrf2-Keap1 Signaling Pathway Regulates Human UGT1A1 Expression in Vitro and in Transgenic UGT1 Mice

Abstract: The formation of ␤-D-glucopyranosides (glucuronides) by the UDP-glucuronosyltransferases (UGTs) is a significant metabolic pathway that facilitates the elimination of small hydrophobic molecules such as drugs, dietary constituents, steroids, and bile acids. We elucidate here that an anti-oxidative response leads to induction of UGT1A1 through the Nrf2-Keap1 pathway. When human HepG2 cells were treated with the prooxidants tert-butylhydroquinone and ␤-naphthoflavone, cellular UGT1A1 glucuronidation activities w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
92
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(94 citation statements)
references
References 41 publications
(50 reference statements)
2
92
0
Order By: Relevance
“…Specificity was further confirmed by the disappearance of the gel shift band in the presence of an antiNrf2 affinity-purified polyclonal antibody (lane 7), whereas no disappearance was seen with the use of a corresponding IgG control (lane 8). Instead of a supershift, the disappearance of the gel shift band suggests a competition for binding between the Nrf2 antibody and NQO1 oligonucleotide, similar to that reported for Nrf2 binding to an antioxidant response element of UGT1A1 with nuclear extracts from HepG2 cells after oxidative stress (38). Figure 3.…”
Section: Validation Of Newly Identified Nrf2-modulated Genessupporting
confidence: 71%
See 1 more Smart Citation
“…Specificity was further confirmed by the disappearance of the gel shift band in the presence of an antiNrf2 affinity-purified polyclonal antibody (lane 7), whereas no disappearance was seen with the use of a corresponding IgG control (lane 8). Instead of a supershift, the disappearance of the gel shift band suggests a competition for binding between the Nrf2 antibody and NQO1 oligonucleotide, similar to that reported for Nrf2 binding to an antioxidant response element of UGT1A1 with nuclear extracts from HepG2 cells after oxidative stress (38). Figure 3.…”
Section: Validation Of Newly Identified Nrf2-modulated Genessupporting
confidence: 71%
“…Newly identified Nrf2-modulated genes were validated with electrophoretic mobility shift assay (37,38). We incubated 10 μg of nuclear extract from small airway epithelium with a 32 P-labeled antioxidant response element oligonucleotide from NAD(P)H dehydrogenase, quinone 1 (NQO1), a known Nrf2-modulated gene (10,37).…”
Section: Validation Of Newly Identified Nrf2-modulated Genesmentioning
confidence: 99%
“…In line with this, the role of Nrf2 in mediating the co-regulation of the phase II enzymes and ABC transporters was further confirmed by the discovery of AREs (antioxidant response elements) in many of these genes. For example, the AREs have been detected in many genes of the phase II enzymes including the GST (Wasserman and Fahl, 1997;Kwak et al, 2003), GCLC (Kwak et al, 2003), and UGT1A1 genes (Yueh and Tukey, 2007); ARE-like sequences were also identified in the mouse ABCCs (Vollrath et al, 2006). These finding suggest that a common regulatory mechanism is possible for the GST, GCLC and ABCC genes (Meijerman et al, 2008).…”
Section: Discussionmentioning
confidence: 96%
“…It is tempting to speculate that evolution of the gtPBREM cluster of binding sites for a number of LATFs in the promoter of UGT1A1 [46,47] may be related to the need for perinatal UGT1A1 induction in primates. This cluster contains binding sites for CAR and PXR [47], AhR [33], Nrf2 [76], PPARα [51] and for the glucocorticoid receptor [47]. It is obvious that perinatal induction represents a stressful condition.…”
Section: Page 9 Of 31mentioning
confidence: 99%